Health behavioral responses to parental myocardial infarction and impact on own risk of disease in the general population - Skouenborg, Christian; Jørgensen, Martin Lucas; Nielsen, Torben Heien; Benn, Marianne (Frontiers in Public Health, 2023)
Aims A family history of coronary heart disease increases one's own risk of experiencing cardiovascular disease and death. An implication of the hereditary nature of the disease is that individuals are provided information about their own risk when a parent is affected, potentially leading them to engage in behaviors that reduce their own risk. In this study, we assessed how a 10-year risk of a cardiovascular event, measured by SCORE, changes for the offspring in response to a parent experiencing a myocardial infarction. Methods We analyzed 19,995 individuals from the general population in the Copenhagen City Heart Study of whom 2,071 had a parent, who suffered from a myocardial infarction during four decades of observation using fixed-effects regressions. Results Following a parental myocardial infarction, individuals reduced their 10-year risk by 0.16 percentage points constituting a 7.1% reduction of baseline risk. Male participants had the largest change in the risk SCORE following an event of the mother, with a 12.4% reduction from the baseline risk. The degree of response contingent on their own level of risk was found to be the largest for individuals with a 10-year risk between 5% and 10%, who also showed a reduction in systolic blood pressure following paternal myocardial infarction. Parental myocardial infarction was associated with an increased smoking rate in individuals with a baseline risk above 10%, while reductions in risk were seen for individuals with a lower baseline risk. Conclusion Following a parental event, individuals reduced their 10-year risk with the largest reductions in their own risk, as observed in men and individuals experiencing a maternal event. The response was the largest for individuals with a 10-year risk for myocardial infarction between 5 and 10%.